2014 IEEE International Conference on Image Processing (ICIP) 2014
DOI: 10.1109/icip.2014.7025920
|View full text |Cite
|
Sign up to set email alerts
|

Image deconvolution using tree-structured Bayesian group sparse modeling

Abstract: In this paper, we propose to incorporate wavelet tree structures into a recently developed wavelet modeling method, called VBMM. We show that, using overlapped groups, tree-structured modeling can be integrated into the highperformance non-convex sparsity-inducing VBMM method, and can achieve significant performance gains over the coefficient-sparse version of the algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…To encourage the persistence of large/small coefficients across scales, where ŵ is a P × 1 vector that forms groups of wavelet coefficients in the non-overlapping space, and the sparse transformation matrix D indicates the presence or absence of correspondence between the overlapping and non-overlapping spaces. Unlike [30], in this paper we construct the D matrix to be a Parseval tight frame such that D T D = I. A simple example of this non-overlapping redundant transformation is shown in Fig.…”
Section: Extension For Tree-structured Modelingmentioning
confidence: 98%
See 3 more Smart Citations
“…To encourage the persistence of large/small coefficients across scales, where ŵ is a P × 1 vector that forms groups of wavelet coefficients in the non-overlapping space, and the sparse transformation matrix D indicates the presence or absence of correspondence between the overlapping and non-overlapping spaces. Unlike [30], in this paper we construct the D matrix to be a Parseval tight frame such that D T D = I. A simple example of this non-overlapping redundant transformation is shown in Fig.…”
Section: Extension For Tree-structured Modelingmentioning
confidence: 98%
“…To achieve the goal of a fully overlapped group sparse solution, it is possible to incorporate the VBMM model with a wavelet tree structure as shown in [30]. Recent works have demonstrated that modeling wavelet parent-children relationships can be viewed as overlapping group regularization [29,43].…”
Section: Extension For Tree-structured Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Hierarchical sparsity was first studied in [44], [45], [46] and later incorporated into a unimodal dictionary learning framework in [47]. Later, Bayesian hierarchical sparse signal recovery techniques were developed, which form the basis for the following derivation [48], [49].…”
Section: B Hierarchical Sparsitymentioning
confidence: 99%